In vivo functional interaction between DNA polymerase and dCMP-hydroxymethylase of bacteriophage T4. - Chao, J (1977)
Some mutations in the structural gene for T4 DNA polymerase (gene 43) behave as suppressors of a deficiency in T4 dCMP-hydroxymethylase (gene 42). The suppression appears to involve a functional interaction between the two enzymes at the level of DNA replication. The hydroxymethylase deficiency caused DNA structural abnormalities in replication, and DNA polymerase lesions appeared to partially reverse these abnormalities. The results do not necessarily imply protein-protein interactions between the two enzymes, although both enzymes appear to play roles in controlling the fidelity of phage DNA replication.